2007
DOI: 10.1124/jpet.106.119115
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transforming Growth Factor β in Rat Bladder Smooth Muscle Cell Proliferation

Abstract: Conditions associated with hypertrophy of the urinary bladder have repeatedly been associated with an increased urinary excretion of transforming growth factor (TGF) ␤ in both rats and patients. Because TGF␤ can have both growth-promoting and -inhibiting effects, we have studied its effects on cell growth and death in primary cultures of rat bladder smooth muscle cells. TGF␤1, TGF␤2, or TGF␤3 did not cause apoptosis, but all three isoforms inhibited DNA synthesis with similar potency (EC 50 of approximately 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In static culture, the α -SMA appeared to be unchanged with the addition of TGF- β 1. An increase in α -SMA expression has been reported previously in static culture of isolated BSMC as well as aortic smooth muscle cells with the addition of TGF- β 1 to culture (Barendrecht et al 2007). TGF- β 1 has also been shown previously to increase cell hypertrophy in an isolated BSMC study (Howard et al 2005).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In static culture, the α -SMA appeared to be unchanged with the addition of TGF- β 1. An increase in α -SMA expression has been reported previously in static culture of isolated BSMC as well as aortic smooth muscle cells with the addition of TGF- β 1 to culture (Barendrecht et al 2007). TGF- β 1 has also been shown previously to increase cell hypertrophy in an isolated BSMC study (Howard et al 2005).…”
Section: Discussionsupporting
confidence: 57%
“…In vitro, we have found that TGF- β 1 alters BSMC phenotype and the organization of the ECM (Parekh et al 2009a,b). In other studies, TGF- β 1 induced hypertrophy, upregulated collagen, and inhibited proliferation of BSMCs (Barendrecht et al 2007), as well as increasing stress fiber expression and reducing gap junctions (Neuhaus et al 2009). TGF- β 1 modulates cellular phenotype in fibrosis (Leask and Abraham 2004) and regulates the RHAMM protein as well as CTGF in the fibrotic bladder (Capolicchio et al 2001; Bagli et al 1999).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, induction of inositol 1,4,5 triphosphate (IP3) stimulates the initial contractile response of bladder smooth muscle [58], and simvastatin has been shown to increase the cellular level of IP3 [59]. Nevertheless, bladder hypertrophy involves several factors, including M2 receptors [60], neurotransmitters like glutamate [61], transcriptional factors like STAT3 [6], nerve growth factor [62], intracellular calcium [34], transforming growth factor beta [63], basic fibroblast growth factor [7], and protein kinase C [64]. Therefore, the exact signaling cascade involved in simvastatin-mediated bladder and renal functional recovery remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor-β (TGF-β) have been shown to regulate cell growth and differentiation in both urothelium and bladder smooth muscle [5]. Studies have shown that TGF-β induced hyperplasia, upregulated collagen, inhibited proliferation of bladder smooth muscle cells [6] and modulated cellular phenotype in fibrosis. It has been shown to regulate connective tissue growth factor (CTGF) in bladder fibrosis [7].…”
Section: Introductionmentioning
confidence: 99%